The ‘I’-Consciousness of the Upanishadic Values in Kamala Das’s Selected Poems (International Journal of Food and Nutritional Sciences, 2022)
It is a general notion that Kamala Das is a poet of confession. She confesses her frustration with physical love and also with social taboos and traditions. Her despondency in her personal life gets a radical change to move forward to the Ultimate Reality. She realizes that gross and sensuous feelings do not permit her to provide absolute happiness that is her prominent aspiration in her life. She desires to transcend her physical identity and sorrow. The present research paper tries to investigate that the ‘I’-Consciousness of the Upanishads felt in her poems helps her to transcend and to reach the way of absolute salvation from physical limitation. The ‘I’-Consciousness is a mystical power and subtle judgement which helps her to discriminate between finer and gross things, temporal and permanent, and ultimately physical body and the Soul residing in human body.